Urgensi Pelestarian Hutan Mangrove sebagai Mitigasi Abrasi di Wilayah Pesisir Lombok - Putri Tiar; Varisha Susan (Journal of Community Development and Empowerment, 2026)
The coastal areas of Lombok Island are facing increasing threats of coastal erosion due to climate change, human activities, and the decline of protective coastal vegetation. Mangrove forests play a crucial role as natural barriers that can reduce wave energy, trap sediments, and maintain the stability of coastal ecosystems. However, the level of public awareness regarding the importance of mangrove conservation remains relatively low in several coastal areas. This community service activity aims to enhance public understanding and participation in preserving mangrove forests as a strategy for mitigating coastal erosion in Lombok’s coastal regions. The methods used include educational outreach, participatory discussions, and mangrove planting activities involving coastal communities. The program engages local community groups, village officials, and youth as partners in its implementation. The results indicate an increase in community knowledge regarding the ecological functions of mangroves and their role in protecting coastal areas. In addition, the hands-on mangrove planting activities have fostered collective awareness and strengthened community commitment to sustainably protect mangrove ecosystems. Active community participation has proven to be a key factor in the success of mangrove conservation efforts as a measure to mitigate coastal erosion. Thus, this community service activity not only provides theoretical understanding but also encourages concrete actions in preserving coastal environments. Moving forward, sustained synergy among communities, government, and related institutions is needed to ensure the continuity of mangrove conservation programs in Lombok’s coastal areas.